Relationship between Person–Environment Fit Types and Turnover Intention: A Moderated Mediation Model - Kerse, Gökhan; Koçak, Daimi; Babadağ, Mustafa (Organizations and Markets in Emerging Economies, 2022)
In this study, drawing on Hobfoll’s Conservation of Resources (COR) Theory, we tested a moderated mediation model that investigates person–organization (PO) fit as the mediator and per- son–job (PJ) fit as the moderator in the relationship between person–supervisor (PS) fit and turnover intention. Data were collected from 232 bank employees in Turkey by using a survey method. Consistent with hypothesized conceptual scheme, results showed that PO fit mediated the relationship between PS fit and turnover intention. Furthermore, moderated mediation results indicate that PJ fit not only moderated the relationship between PS fit and PO fit but also reinforced the indirect effect of PS fit on turnover intention (via PO fit). We argue that indirect effect of PS fit on turnover intention through PO fit was stronger for employees with high job fit than for employees with low job fit. The theoretical and practical implications, limitations, and future research directions are also discussed.